Workaholism and Work-life Imbalance : The Potential Influence on Health Variables - Hartinger, Jenna (East Carolina University, 2010)
The purpose of this study was to determine if the dimensions of workaholism (i.e., compulsive tendencies, control, and impaired communication/self-absorption), as measured by Robinson's (1996) Work Addiction Risk Test, and work-life imbalance were related to health variables such as BMI, weekly exercise, and the existence of health issues (e.g., self-report and/or family history of Type II diabetes, heart disease, high cholesterol). The dimensions of the WART and work-life imbalance were used as predictors and the health variables were used as the criteria. Personal demographic variables (e.g., age, gender, race, marital status) served as the control. The results indicated that there were numerous relationships between the workaholism and work-life imbalance variables and the health variables. The compulsive tendencies dimension, control dimension, and total WART score were significantly positively related to family history of heart disease and family history of high cholesterol. Work-life imbalance was significantly positively related to high cholesterol. Study limitations, directions for future research, and practical implications are discussed.
Keywords: Occupational psychology; Workaholism; Workaholics--Health risk assessment; Compulsive behavior; Work-life balance